Electrical Demand Analysis on Households and Industry in Indonesia - Kartika, Margareth; Hidayati, Nur Aini (Department of Economics, Faculty of Economics and Business, Universitas Airlangga, 2024)
This research aims to determine the response of the household sector and industrial sector to electricity demand when there are changes in prices and income. The influence of price and income on electricity demand from both sectors can be seen through their elasticity. The approach used in this study is panel data from 33 provinces in Indonesia for the 2010-2020 time period. Panel data regression estimation techniques are used in this study to estimate the elasticity value. The results show that price elasticity in the household and industrial sectors is negative inelastic, but price does not significantly influence household electricity demand. Unlike price, income elasticity has a much higher value and positively and significantly influences electricity demand in both sectors. The number of customers, which reflects the increasing electrification ratio and population growth, significantly impacts electricity demand in the household and industrial sectors. Based on the results, it was found that the number of customers most influences electricity demand in the household sector. At the same time, income has the most significant influence on electricity demand in the industrial sector.